Handbook on the Use of Pesticides in the Asia-Pacific Region - Asian Development Bank (Philippines: Asian Development Bank, 1987)
The book is a detailed review on regulation of pesticides in selected member countries with recommendations on how the Bank should proceed to ensure environmentally sound practices in its agricultural projects.
Includes bibliographical references
rua 14/06/17
Loans.
Keywords: Pesticides; Asia; Pacific Area